The Multinational Motor Industry. - Maxcy, George (Routledge Library Editions: International Business., 2013)
This book analyses the multinational enterprise using the example of the world motor industry. It begins by examining the multinational enterprise in general, considering its nature, the economic theory of its behaviour and is effects on the nation state. It goes on to explore the growth and development of the multinational motor industry, and then surveys the state of the motor industry, and the role of multinationals in it, in various types of economy, using case studies from the UK, USA, Canada, Australia, Brazil and India.